Rosalydia, a new genus of Neocoelidiinae (Hemiptera: Cicadellidae) from Brazilian Amazon, with description of three new species - Gonçalves, Clayton Corrêa; Viegas, Eduarda Fernanda Gomes (Zootaxa, 2022)
A new neocoelidiine leafhopper genus from the Brazilian Amazon, Rosalydia gen. nov., is described based on three new species: R. alvarengai gen. et sp. nov. from the state of Mato Grosso, R. inpa gen. et sp. nov. and R. xavieri gen. et sp. nov. from the state of Amazonas. An identification key to species of Rosalydia gen. nov. is provided.